The Colonial Hotel: spacing violence at the Grande Hotel, Beira, Mozambique. (April 2019) - Sarmento, João; Linehan, Denis
In spite of its dereliction, the Grande Hotel in Beira, Mozambique, has emerged as an iconic African building. The dissonant meanings of this site, offer multiple opportunities to investigate the intersection of space and colonialism. We focus upon the cultural and political topologies of the hotel, and of colonial hotels generally, and make the proposition that they were a particular kind of violent colonial institution. By converging a relational reading of both violence and architecture, we reconstruct through the excavation of archival and related materials, the processes present in the histories of the hotel and city at large, to unmask how they acted as spaces of slow violence. White settler's activities and rationales were underpinned by deliberative strategies of unknowing, forgetting, disavowal which together formed a kind of cultural agnosia that insulated them from the foundational violence that supported the colonial condition. We use a dispersed concept of violence, understood as a tactical and mutable process, which moves between physical, symbolic, embodied and performative domains. We address these domains in the paper through an analysis of the ways the city of Beira was planned, its architecture shaped and represented, and in the recreational and social performances within the hotel.